Smectite as a marker of telogenetic process along structural heterogeneities of sedimentary basin: case study of the Eocene submarine slide surfaces of the Ainsa Basin - Odonne Francis; Beaufort Daniel; Munck Romain; Bourrières Laure; Darrozes José (BSGF - Earth Sciences Bulletin, 2017)
Fluid circulation in sedimentary basins is responsible for the transformation and cementation of mineral grains during diagenesis. Concretions and pipe chimneys are obvious features resulting from such circulation but some transformations in the matrix of rocks, if less spectacular, may lead to pervasive transformations of the sediments. Inherited slide surfaces in the Eocene Ainsa Basin (Spanish Pyrenees) have been chosen to test this hypothesis. In the Sobrarbe delta, the steady mineralogy of marls indicates homogeneity of the sedimentary source. Enrichment of montmorillonite is only observed close to scar surfaces and in the infilling of the scars. Scanning electron microscope (SEM) observation reveals that smectites are formed by in situ replacement of detrital mafic minerals resulting by transformation of detrital minerals under the action of cold sedimentary fluids, lower than 75 °C. The indications of low temperature conditions and local fluid circulation both support a meteoric origin of the fluids postdating the burial history, probably during an exhumation of the basin associated with the tectonic uplift. The higher smectite contents in the infilling of scars and along the unconformities of slide surfaces reveals enhanced circulation of fluids in under-consolidated sediments and the effective fluid circulation pathways along inherited slide surfaces.